Delayed diagnosis of angioimmunoblast T-cell lymphoma presenting with immunoglobulin a vasculitis - Lu Xu; Huihui Dong; Dandan Xue; Yiming Zhang; Xinjian Li (Renal Failure)
Although vasculitis and renal involvement might be associated with malignancy, they are rarely associated with lymphoproliferative diseases. We observed a case of immunoglobulin A vasculitis associated with segmental and focal glomerulonephritis in a patient with Angioimmunoblastic T-cell lymphoma. The most interesting aspect of this case is that this patient’s main initial manifestations were skin rash and fever. No significant lymph node enlargement was found at the time. Routine urine examination found positive urine protein, and renal puncture biopsy indicated purpura nephritis. More than one year later, the patient was admitted to the Department of Hematology of our hospital again after finding a mass in the neck. After that, the patient was diagnosed with Angioimmunoblastic T-cell lymphoma by lymph node biopsy. To our great surprise, successful treatment of the underlying malignancy was associated with the remission of glomerulonephritis and cutaneous vasculitis.